The correlation of health spending and infant mortality rate in Asian countries - Shetty, Anil; Shetty, Shraddha (International Journal of Contemporary Pediatrics, 2017)
Background: Infant Mortality Rate (IMR) is one of the most vital health indicators. A number of factors impact and influence IMR. One of the most important ones could be public health spending. Health spending however is not uniform throughout Asia and varies from region to region. Methods: Data obtained from the World Health Organization and World Bank Databases were used to assess the effect of state health spending on IMR. Factors such as per capita spending on health, proportion of GDP directed at health and private spending as a percentage of total health spending and their influence on IMR were also studied. Results: Data from 34 Asian countries was included in the study. Singapore (2) and South Korea (3) had the least IMR in the region. Afghanistan (71) had the highest IMR and also the least per capita governmental spending on health and Qatar the highest spending on health. Conclusion: Per capita state spending on health was the most important determinant of IMR in our study and countries with higher per capita spending on health had significantly lower levels of IMR.